Health Care Center - Alawneh, Mohammed; Kamal, Sameh; Assi, Hamza (My University, 2017)
There is an urgent need to improve the medical and health services provided to people in Palestine and to make it efficient and as near as possible to people’s living areas. a large number of accidents happens on the road between Nablus and jenin city every year ,taking into consideration that the closest health facilities are in the cities. Which making the need for health care center especially with an emergency section is very important. A design for a health care center was done in the middle between Nablus and jenin city in jabaa village to cover the health deficiencies in the region and provide the essential health care people needs in the village and the surrounding villages. the level of services safety standard and public facility provided were improved in an integrated way which includes architectural, structural, electrical, environmental, mechanical, and safety aspects a great challenge to create a desirable place with a noise reduction, economically, environmentally-friendly and comfortably. Architecturally, a design of three floors including the emergency section , clinical rooms, x-ray and lab. taking into consideration that the distribution of spaces was according to their functions and the orientation of the health center. The Architectural design was done by Revit program for 3-D models and AutoCAD for 2-D plans. Structurally, structural design built by Etabs , taking into account the most appropriate type of design. Environmentally, through INSUL program the sound transmission class were dedicated for interior and exterior walls, heating, cooling and day lighting design were done through Design Builder program, day lighting factor, RT60 and U-Value were done in ECOTECT. Electrically, types of lamps, uniform distribution for lamps, were designed through DIALUX EVO. Mechanically, diameter of pipes, size of ducts and type of HVAC system, drainage and water supply systems were calculated and chosen appropriately.